2020
DOI: 10.18203/2349-3291.ijcp20202622
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency among hospitalized infants with acute lower respiratory tract infection

Abstract: Background: Vitamin D plays important role in immunity and its deficiency might be associated with increased risk of lower respiratory tract infection. This study aimed to determine whether vitamin D deficiency is commoner in infants with acute lower respiratory tract infection as compared to normal infants and to correlate the severity of vitamin D deficiency with severity of ALRTI.Methods: A hospital based prospective case-control study was conducted in a tertiary care hospital. A total of 208 infants (109 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In recent era, micro-nutrients are playing a major role as potential adjunctive immunotherapy to the polyvalent actions of vitamin D for human deficit has been looked into and has been associated with a number of different diseases 11 . Most of the studies had concluded that decreased serum concentration of vitamin D is associated with increased rate of respiratory tract infections and decreased levels of vitamin D is seen in children with respiratory tract infections 12 . According to the study done by Bergman et al it includes 11 randomized placebo controlled trials.…”
Section: 1mentioning
confidence: 99%
“…In recent era, micro-nutrients are playing a major role as potential adjunctive immunotherapy to the polyvalent actions of vitamin D for human deficit has been looked into and has been associated with a number of different diseases 11 . Most of the studies had concluded that decreased serum concentration of vitamin D is associated with increased rate of respiratory tract infections and decreased levels of vitamin D is seen in children with respiratory tract infections 12 . According to the study done by Bergman et al it includes 11 randomized placebo controlled trials.…”
Section: 1mentioning
confidence: 99%